Analysis of Newton’s Laws Concepts in Besei Kambe: A Traditional Sport of Central Kalimantan - Agitha Anastasya; Ani Rusilowati; Budi Astuti (Jurnal Penelitian Pendidikan, 2026)
Besei Kambe is a traditional Dayak game from Central Kalimantan in which two teams compete by pulling a jukung on the water. Beyond its cultural significance, this activity embodies various physics concepts that can be utilized as contextual learning resources. This study aims to identify and analyze the physical principles that emerge during the practice of Besei Kambe, particularly those related to Newton’s laws, action–reaction forces, and resultant forces. Through qualitative analysis based on illustrative observation and literature review, the study reveals that the motion dynamics of the boat and the interactions between the paddlers and the water reflect direct applications of these fundamental physics concepts. These findings indicate Newton’s First Law appears when the boat remains still under balanced forces, Newton’s Second Law when an unbalanced force causes acceleration, and Newton’s Third Law in the action–reaction interaction between the paddle and the water. These findings demonstrate that Besei Kambe naturally represents fundamental mechanics principles and can serve as an effective contextual resource for physics learning grounded in local wisdom.